Influence of infrastructure institutions on the dynamics of agricultural production development in Kazakhstan - Zhanseitov, А.Т.; Saparova, G.K.; Myrzhykbayeva, A.B. (BUKETOV BUSINESS REVIEW, 2024)
Object: to assess the impact of infrastructural institutions on the development of rural production, as well as to investigate the present results in agricultural production and its prospects. Methods: the system-functional approach was used as a general method, as well as general scientific methods: abstract-logical, dialectical; methods of statistical analysis. Results and conclusions. Findings: technology, infrastructure, and market strategies all play a role in fostering agricultural growth for the benefit of the broader population at all developmental phases. Insufficient infrastructure stands out as a significant barrier to the effective advancement of the agro-industrial sector. Investing public funds into infrastructure holds significance in establishing favorable conditions for financial markets to operate effectively in rural regions. Enhancing rural infrastructure also incentivizes commercial entities to extend favorable loan terms to farmers, as the associated risks diminish. Furthermore, a pivotal determinant of international competitiveness lies in the presence of sufficient and efficient national infrastructure. Conclusions: enhancing national infrastructure can bolster international competitiveness through several avenues, including boosting price competitiveness, enhancing non-price competitiveness, and attracting foreign direct investment (FDI).